Modeling the Impact of Hedonic Motivation, Consumer Lifestyle, and Promotions on Impulsive Buying: The Mediating Role of Positive Emotions - Rahmawati, Selly Putri; Mawardi, M. Cholid; Hardaningtyas, Ratna Tri (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study focuses on analyzing the role of positive emotions as a mediator in the relationship between hedonic shopping motivation, consumer lifestyle, and promotion with impulsive buying at OH!SOME Malang Town Square. The method used is explanatory research with purposive sampling of 135 respondents aged at least 17 years who have shopped at the location. Data were obtained using an online questionnaire and subsequently analyzed using SEM-PLS. The validity and reliability of the data were tested using CFA and Cronbach's Alpha.  It was determined that impulsive purchasing was not influenced by hedonistic shopping motivation or lifestyle, but rather by positive emotions and promotions.  The relationship between hedonistic purchasing motivation, lifestyle, and promotions with impulsive buying was discovered to be mediated by positive emotions. These findings are expected to assist OH!SOME management in designing more effective marketing strategies and better understanding consumer behavior.